2017
DOI: 10.1002/jmri.25600
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion diffusion‐weighted imaging of bone marrow in patients with acute myeloid leukemia: a pilot study of prognostic value

Abstract: 1 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2017;46:476-482.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…IVIM simultaneously permits quantification of perfusion as well as diffusion using a single imaging scan . The perfusion information is useful for the assessment of inflamed synovitis in RA because an increased number/area of capillaries is observed in the inflamed synovial membrane as compared with the normal synovial membrane .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IVIM simultaneously permits quantification of perfusion as well as diffusion using a single imaging scan . The perfusion information is useful for the assessment of inflamed synovitis in RA because an increased number/area of capillaries is observed in the inflamed synovial membrane as compared with the normal synovial membrane .…”
Section: Discussionmentioning
confidence: 99%
“…Intravoxel incoherent motion (IVIM) analysis, as originally described by Le Bihan et al, is a method based on DWI with multiple b values that assumes a relationship between the signal intensity and the b value . IVIM simultaneously permits quantification of both diffusion and perfusion using a single imaging study, without the need for intravenous contrast injection . A recent study by Hilbert et al suggested that IVIM improves the diagnostic performance and diagnostic confidence via improved visual separation of inflamed synovium and joint effusion as compared with DWI alone in the knee joint of children with juvenile idiopathic arthritis .…”
mentioning
confidence: 99%
“…One study analyzed IVIM parameters prior to chemotherapy and looked at the differences between complete remission and nonremission groups. 71 Interestingly, in the complete remission group they found that D was significantly higher (0.24 AE 0.04 vs. 0.20 AE 0.03 × 10 −3 mm 2 /s) and f was significantly lower (22.38 AE 5.19 vs. 27.89 AE 8.25 × 10 −3 mm 2 /s) than in the nonremission group. Because ADC had not shown significant differences, they suggested D and f values could be used as biomarkers to prognosticate AML.…”
Section: Ivim For Osseous Tumor Gradingmentioning
confidence: 89%
“…In acute myeloid leukemia (AML), high cellularity and angiogenesis of marrow are regarded as a poor prognosis. One study analyzed IVIM parameters prior to chemotherapy and looked at the differences between complete remission and nonremission groups . Interestingly, in the complete remission group they found that D was significantly higher (0.24 ± 0.04 vs. 0.20 ± 0.03 × 10 −3 mm 2 /s) and f was significantly lower (22.38 ± 5.19 vs. 27.89 ± 8.25 × 10 −3 mm 2 /s) than in the nonremission group.…”
Section: Intravoxel Incoherent Motion (Ivim)mentioning
confidence: 99%
“…As a result, the IVIM technique can now be applied to various tissues. Surprisingly, however, only a very limited number of IVIM studies have been performed on bone marrow . This might be due to lipids, which represent a major confounding factor in the quantification of both diffusion and perfusion .…”
mentioning
confidence: 99%